Biodiversity through Domestication - Wulf Schiefenhövel (Revue d'ethnoécologie)
It is not widely known that Melanesia became a centre of horticulture and arboriculture about 8,000 years ago: taro (Colocasia esculenta, Cyrtosprema chamissonis, Alocasia macrorrhiza); sugar cane (Saccharum officinarum), a close relative called sayur lilin in Bahasa Indonesia, respectively pitpit in Neomelanesian Pidgin (Saccharum edule) of which the young inflorescence is eaten; yams (Dioscorea bulbifera and possibly other species like D. alata); banana (Musa spp., comprising Australimusa and Eumusa); two or more Setaria species (Setaria palmifolia, Setaria plicata...); beans of the genus Phaseolus; probably Rungia klossii and Abelmoschus manihot (cp. Okra, the also edible fruit of this plant), both green leafy vegetables with a high content of protein and minerals; sago (Metroxylon sagu, possibly also other species); several species of the genus Pandanus (e.g. P. brosimos and P. conoideus); breadfruit (Artocarpus altilis); the so-called Tahitian chestnut (Inocarpus fagifer); nut bearing trees like the Okari nut (Terminalia kaernbachii) and nuts of the genera Canarium and Spondias; coconut (Cocos nucifera) which was probably cultivated in island Melanesia or Polynesia. A number of these domesticated species, e.g. taro, sugar cane, Rungia klossii, other vegetables and nut-bearing trees were domesticated in isolated Highland New Guinea. Biodiversity was thus, by the gardening activities of ancestral Papuan peoples, increased in this part of the world. In some regions, which are not accessible by road as yet, this rich human-made biodiversity may survive for some time.